2020
DOI: 10.1186/s12937-020-00539-7
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of a randomised controlled trial investigating the effect of multidisciplinary nutritional rehabilitation for patients treated for head and neck cancer (the NUTRI-HAB trial)

Abstract: Background: Eating problems frequently affect quality of life and physical, psychological and social function in patients treated for head and neck cancer (HNC). Residential rehabilitation programmes may ameliorate these adverse effects but are not indicated for all individuals. Systematic assessment of rehabilitation needs may optimise the use of resources while ensuring referral to rehabilitation for those in need. Yet, evidence lacks on which nutrition screening and assessment tools to use. The trial object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 75 publications
1
14
0
Order By: Relevance
“…In a pilot study testing a 1-week residential psychoeducational program in HNC survivors, high participant satisfaction and improvements in QOL scales were reported [19]. In another pilot study conducted by the researchers behind the present trial, qualitative data showed that HNC survivors benefitted from participating in a multidisciplinary residential nutritional rehabilitation program [4], and significant improvements in body weight and several QOL scales were seen at the 3-month follow-up [24]. With no control group in any of the pilot studies, the effect of residential rehabilitation programs in HNC survivors should be tested in randomized controlled trials.…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…In a pilot study testing a 1-week residential psychoeducational program in HNC survivors, high participant satisfaction and improvements in QOL scales were reported [19]. In another pilot study conducted by the researchers behind the present trial, qualitative data showed that HNC survivors benefitted from participating in a multidisciplinary residential nutritional rehabilitation program [4], and significant improvements in body weight and several QOL scales were seen at the 3-month follow-up [24]. With no control group in any of the pilot studies, the effect of residential rehabilitation programs in HNC survivors should be tested in randomized controlled trials.…”
Section: Introductionmentioning
confidence: 61%
“…The detailed trial protocol [24] was developed in accordance with the standard protocol items for randomized trials (SPIRIT) 2013 [25,26] statement, the consolidated standards of reporting trials (CONSORT) extension for reporting trials of nonpharmacologic treatments [27], and the template for intervention description and replication (TIDieR) [28] checklist and guide. An overview of trial materials and information on how to obtain these have been published with the trial protocol [24]. The CONSORT 2010 statement [29] and the CONSORT extension for reporting trials of nonpharmacologic treatments [27] were used as guidelines for reporting trial results.…”
Section: Trial Designmentioning
confidence: 99%
See 3 more Smart Citations